Effects of air pollution on the development and progression of digestive diseases: an umbrella review of systematic reviews and meta-analyses - Haonan Zhao; Xiaojie Zheng; Guo Lin; Xiaomin Wang; Huiyuan Lu; Pengpeng Xie; Siqi Jia; Yiyang Shang; Yan Wang; Pengchu Bai; Xuan Zhang; Ning Tang; et al. (BMC Public Health)
Abstract Air pollution, especially particulate matter (PM), is one of the most common risk factors for global burden of disease. However, its effect on the risk of digestive diseases is unclear. Herein, we attempt to explore this issue by reviewing the existing evidence from published meta-analyses. We conducted a systematic literature search to identify all relevant meta-analyses regarding the association of air pollution with digestive diseases, and summarize their major findings. We assessed the methodological quality and evidence quality of the included meta-analyses using the AMSTAR-2 and GRADE tools, respectively, and the overlap of primary studies was assessed by the GROOVE tool. Nine meta-analyses were included in our analysis, containing 43 primary studies with high overlap. In the included meta-analyses, the methodological quality was from critically low to moderate, and the evidence quality was from very low to moderate. The exposure was primarily PM2.5. Seven, four, and one meta-analysis investigated the effect of air pollution on liver diseases, gastrointestinal diseases, and pancreatic diseases, respectively. PM2.5 exposure was significantly associated with liver dysfunction, chronic liver diseases, liver cancer, and colorectal cancer, but not oesophagus cancer, gastric cancer, or pancreatic cancer. Based on very low to moderate quality evidence from meta-analyses, PM2.5 exposure may contribute to the development of some digestive diseases, especially liver diseases.